Analysis Of The Effectiveness Of Corruption Investigation By The National Police In The Recovery Of State Financial Losses - Salupen; Nashriana; Mada Apriandi Zuhir (Faculty of Law, Universitas Pekalongan, 2024)
Corruption is a serious issue that threatens the nation's finances, making the recovery of state financial losses crucial. This study aims to analyze the mechanism for the recovery of state financial losses during the investigation stage of corruption by the Indonesian National Police investigators. The issues discussed include the effectiveness of the existing mechanism, the obstacles faced by investigators, and the future regulations needed to improve the recovery process. The research methodology used is a qualitative approach with data analysis through interviews and document studies. The results indicate that although there is a mechanism regulated by laws, there are still many obstacles hindering the recovery process, such as a lack of resources and coordination between institutions. The conclusion of this study recommends strengthening regulations and enhancing the investigators' capacity to expedite the recovery of state financial losses back into the state treasury.